From design to value: How virtual field trip design creates presence and shapes perceived learning value in tourism and hospitality education - Abdallah, Ali (International Journal of Educational Technology and Learning, 2026)
Virtual field trips have transitioned from emergency contingency measures to established pedagogical options in higher education, yet their educational value remains highly variable. This article develops and empirically supports a design-presence-value pathway that explains why some virtual field trips are perceived as meaningful learning experiences while others are experienced as passive and forgettable. Drawing on qualitative focus group data collected from tourism and hospitality students (N = 42) across three higher education institutions, the study synthesises student accounts into an integrative model linking design features to perceived presence and perceived learning value. The analysis reveals that learning value is strengthened when virtual field trips are designed to create presence through high system quality, purposeful instructional organisation, and socially enabling interaction. Students describe presence as feeling involved, attentive, and able to imagine being at the site, whereas low presence is associated with poor audio-visual quality, monotonous delivery, weak structure, and limited opportunity for interaction. The study also identifies distinctive strengths of virtual field trips, including flexibility, accessibility to remote or restricted sites, and replayability. A practical set of design principles is proposed that leverages these affordances while addressing common deficits, particularly the loss of social and networking opportunities. The article offers actionable guidance for educators designing or selecting virtual field trips and provides a theoretically grounded explanation of how instructional design choices translate into student-perceived learning value.